Effect of low dose, short-term creatine supplementation on muscle power output in elite youth soccer players - Aquiles Yáñez-Silva; Cosme F. Buzzachera; Ivan Da C. Piçarro; Renata S. B. Januario; Luis H. B. Ferreira; Steven R. McAnulty; Alan C. Utter; Tacito P. Souza-Junior (Taylor & Francis Group, 2017)
Background To determine the effects of a low dose, short-term Creatine monohydrate (Cr) supplementation (0.03 g.kg.d−1 during 14 d) on muscle power output in elite youth soccer players. Methods Using a two-group matched, double blind, placebo-controlled design, nineteen male soccer players (mean age = 17.0 ± 0.5 years) were randomly assigned to either Cr (N = 9) or placebo (N = 10) group. Before and after supplementation, participants performed a 30s Wingate Anaerobic Test (WAnT) to assess peak power output (PPO), mean power output (MPO), fatigue index (FI), and total work. Results There were significant increases in both PPO and MPO after the Cr supplementation period (P ≤ 0.05) but not the placebo period. There were also significant increases in total work, but not FI, after the Cr supplementation and placebo periods (P ≤ 0.05). Notably, there were differences in total work between the Cr and placebo groups after (P ≤ 0.05) but not before the 14 d supplementation period. Conclusion There is substantial evidence to indicate that a low-dose, short-term oral Cr supplementation beneficially affected muscle power output in elite youth soccer players.